UZBEK LITERATURE. - Durdonaxon Gaziyeva Umidovna; Usmonov Sherzod Rahimjonovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This academic article explores the evolution of Uzbek literature from its roots in ancient oral traditions to the modern literary era. It begins with an examination of heroic epics such as "Alpomish" and continues through the classical Golden Age under Alisher Navoi, who laid the foundations of Chagatai literature. The paper analyzes literary developments during the periods of the Bukhara, Khiva, and Kokand Khanates, followed by the Jadid reformist movement and the impact of Soviet ideology on literary production. It also delves into the revival of national literature after Uzbekistan’s independence in 1991, highlighting the emergence of postmodernist techniques, themes of identity and spirituality, and the growing role of female authors. Central themes include patriotism, historical memory, social criticism, and the enduring connection between literature and Uzbek cultural identity. The paper emphasizes how Uzbek writers continue to engage with global literary trends while preserving their national literary heritage.